Clinical Evaluation of on-Table Extubation in Patients Aged Over 60 Years Undergoing Minimally Invasive Mitral or Aortic Valve Replacement Surgery - Ge, Yunfen; Chen, Yue; Hu, Zhibin; Mao, Hui; Xu, Qiong; Wu, Qing (Frontiers in Surgery, 2022)
Abstract Aims: To evaluate the clinical efficiency of on-table extubation (OTE) versus delayed extubation in patients aged over 60 years that underwent minimally invasive mitral or aortic valve replacement surgery and evaluate the factors associated with successful OTE implementation. Materials: Patients over 60 years with mitral or aortic valve disease who received minimally invasive mitral or aortic valve replacement surgery from October 2020 to October 2021 were selected. We divided patients into the on-table extubated (OTE) group (n=71) and the delayed extubation (DE) group (n=22). Preoperative, intraoperative, and postoperative clinical variables were compared between the two groups. Results: Patients in the DE group underwent longer surgery time, longer aortic occlusion clamping time and longer cardiopulmonary bypass time than those in the OTE group (p<0.05). Patients in the OTE group had shorter postoperative mechanical ventilation time (min), shorter ICU time, shorter postoperative hospital length of stay and lower total cost and medication cost (p<0.05). The AUC for aortic occlusion clamping time was 0.81 (p<0.01), making it the most significant predictor of on-table extubation success. Conclusions: On-table extubation following mitral or aortic valve cardiac surgery was associated with a superior clinical outcome and high cost-effectiveness.